Features of heart and vascular remodeling in patients who have had coronavirus disease - Vozniuk, Olga (The Ukrainian Scientific Medical Youth Journal, 2025)
The aim is to study the impact of COVID-19 on the state of heart and vascular remodeling in patients with coronary heart disease and arterial hypertension. During 2024-2025, 50 people (30 men and 20 women aged 64,2±3,1 years) with coronary heart disease and arterial hypertension were examined one month after treatment for coronavirus disease. In the examined patients after the transferred coronavirus disease on the background of existing hypertension and ischemic heart disease, 52,0 % had left ventricular hypertrophy and changes in the circadian rhythm of blood pressure, in 46,0 % – thickening of the intima-media complex. Among all patients with LV hypertrophy, concentric remodeling (in 23,1 %) and hypertrophy (in 34,6 %), as well as eccentric hypertrophy (in 42,3 % of cases) were found. Such diurnal BP profiles among individuals with concentric remodeling and hypertrophy, as well as with eccentric hypertrophy, as non-dipper were found in 50,0, 33,3 and 36,4 %, night-peaker – in 16,7, 11,2 and 18,2 %, dipper – in 33,3, 55,5 and 45,4 % of the examined. An increase in the thickness of the intima-media complex in eccentric and concentric hypertrophy and in individuals with concentric remodeling was observed in 36,3; 22,2 and 50,0 % of cases. Ultrasound examinations of the heart and blood vessels, their ability to qualitatively and quickly assess the morpho-functional state, the nature of hemodynamics, the risk of possible complications should be used in the diagnosis and treatment of persons with a history of coronavirus disease at the stage of primary medical care.